1874 Va. L. 239, ch. 239 - (:unkn) unknown (My University, 1874)
Included the value of all "rifles, muskets, and other fire-arms, bowie-knives, dirks, and all weapons of a similar kind" in list of taxable personal property.
Keywords: TAX - PROPERTY OR SALES